GUIDANCE AND COUNSELLING SERVICES: A PANACEA TO THE SPIRIT OF NATIONAL UNITY AMONG NIGERIAN STUDENTS - Abdulkareem, Adedayo Yusuf; ABDULRASAQ, ABDULKADIR OLAREWAJU (Sokoto Educational Review, 2018)
This paper highlights the roles that guidance and counselling sendees can play in inculcating the spirit of national unity among Nigerians. It focuses on the meaning of guidance and counselling, the need for guidance sendees in schools. (It further lays emphasis on the unity of Nigeria as exemplified by our lingua franca, currency, National Anthem and Constitution). It further lays emphasis on the roles of the Counsellor on providing a setting that can encourage youth to examine the values, they hold regarding unity among themselves and to train their parents for better family management which offers the greatest promise for averting or reducing the problem of disunity among Nigerian students.